Placebo Response in Patients with Oral Therapy for Overactive Bladder: A Systematic Review and Meta-analysis - Mostafaei, Hadi; Janisch, Florian; Mori, Keiichiro; Quhal, Fahad; Pradere, Benjamin; Hajebrahimi, Sakineh; Roehrborn, Claus G; Shariat, Shahrokh F (European urology focus, 2022)
CONTEXT: The role of a placebo response in the management of overactive bladder (OAB) remains unclear. OBJECTIVE: The aim of this review is to methodically study the placebo response extracted from the control arms of randomized clinical trials assessing therapy in patients with OAB. EVIDENCE ACQUISITION: Medline (PubMed), The Cochrane Library, EMBASE, and Scopus were searched to identify randomized controlled trials (RCTs) published until September 2019. Randomized placebo-controlled trials investigating oral drug therapy for OAB were included. The articles were critically appraised by two reviewers. The primary outcomes were the placebo response in the main patient-reported urinary outcomes together with assessing the impact of patient demographic factors on the placebo response. EVIDENCE SYNTHESIS: The initial search resulted in 1982 records after reviewing the titles and abstracts, and reference lists of other systematic reviews; 57 studies with an overall estimated 12 901 patients were included in the meta-analysis. The included studies were of overall high/acceptable quality. The standardized mean difference was -0.45 (95% confidence interval [CI] -0.51 to -0.40; p<0.001) for daily micturition episodes, -0.33 (95% CI -0.42 to -0.24; p<0.001) for daily nocturia episodes, -0.46 (95% CI -0.55 to -0.37; p<0.001) for urgency urinary incontinence episodes, -0.50 (95% CI -0.61 to -0.39; p<0.001) for daily urgency episodes, -0.51 (95% CI -0.60 to -0.43; p<0.001) for daily incontinence episodes, and 0.25 (95% CI 0.211-0.290; p<0.001) for volume voided per micturition. The meta-regression of age-related impact of the placebo response on nocturia showed a slope of -0.02 (p<0.001). CONCLUSIONS: Placebo has a statistically significant effect on improving symptoms and signs associated with OAB; this effect is age dependent. However, there is no consensus on what change of OAB symptoms and signs is clinically meaningful for the affected patient. Taken together, the placebo response seems to be non-negligible in OAB, supporting the need for placebo control in RCTs. PATIENT SUMMARY: Placebo is an inert treatment method often used in clinical research for comparison with active treatment. However, studies show that placebo has an effect of its own. A placebo response means the total improvement resulting from receiving a placebo. In our study, placebo had a significant role in improving the symptoms of overactive bladder.
Keywords: hyperaktivní močový měchýř; Placebo response; Nocturia; Systematic review; Overactive bladder; Humans; lidé; Placebo Effect; Randomized Controlled Trials as Topic; placebo efekt; Urinary Bladder, Overactive; randomizované kontrolované studie jako téma; nykturie